Broadening Horizons: Is There a Place for Peace Education in the American Legal System and More Specifically in Family Law? - McFarland, MiaLisa (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
The United States legal system is generally perceived by the public both in the national and international arena in a discouraging light. The perception is that litigation is not only expensive and time consuming, but it also furthers contention between parties. There are other methods, referred to as Alternative Dispute Resolution that are being employed by the court system in order to provide solutions to disputes with a greater focus toward “peace and justice simultaneously through the use of a variety of different forms of dialogue, policy-making, rule development, dispute settlement and conflict management.”